(untitled) (International Journal of Physiotherapy, 2017)
Background: This study targeted at finding out the response of the vertebral artery blood flow to Low-Level Laser Therapy (LLLT) in elderly with cervical spondylosis. Methods: Research involved forty patients, both men, and women, whose ages between 60 and 75 years, diagnosed as chronic cervical spondylosis associated with vertigo. Subjects were randomly assigned to two equivalent groups. Group (1), Study Group, received low-level laser therapy (LLLT) with a wavelength of 830 nm and power of 200 mW on vertebral artery bilaterally. Group (2), the control group, received only sham laser (placebo). Both groups received three sessions per week for two months. Blood flow in both vertebral arteries was estimated by measuring Resistivity Index using ultrasound Doppler, and vertigo was assessed by visual vertigo analogue scale. The assessment was done pre and post-treatment. Results: The outcomes of this study revealed highly significant difference between G1 and G2 in post-treatment values of resistivity index of both left and right vertebral arteries (p=0.0008 & 0.0002 respectively) as well as in visual vertigo analogue scale (p=0.0001), while comparing pretreatment values showed no significant differences between G1 and G2 (p=0.329, 0.3795 & 0.2518 respectively). In study group (G1), there was a significant decrease in resistivity index of both left and right vertebral arteries, as well as significant decrease in vertigo. Percentages of improvement were (↓12.28%), (↓13.98%) and (↓64.24%) respectively, which means enhancement of blood flow through vertebral arteries. While (G2) showed a non-significant decrease in resistivity index of the left vertebral artery (↓3.96%), right vertebral artery (↓2.87%), and vertigo (↓10.22%). Conclusion: LLLT with parameters used in this study, improved blood flow through vertebral artery bilaterally and alleviated vertigo in elderly with cervical spondylosis.